Organocatalytic Reduction of Nitroarenes with Phenyl(2‐quinolyl)methanol - Giomi, Donatella; Ceccarelli, Jacopo; Salvini, Antonella; Brandi, Alberto (ChemistrySelect (Weinheim), 2020)
The transition metal free reduction of aromatic/heteroaromatic nitro compounds to amines has been improved employing phenyl(2‐quinolyl)methanol (PQM) as organocatalyst in the presence of NaBH4 or NaCNBH3 as stoichiometric reducing agent. The procedure is chemoselective for NO2 group reduction with high tolerance of many functionalities. The reaction pathway strongly depends on the substituents present on the nitroarene ring. However, a careful choice of the reaction conditions allows to address the reduction process towards the corresponding anilines (isolated in 17–91 % yields). The use of substoichiometric amounts of PQM allows more sustainable processes: reaction products are easily isolated and PQM can be directly recovered at the end of the reaction and recycled. Transition metal free reductions of nitroarenes with phenyl(2‐quinolyl)methanol (PQM) as organocatalyst have been performed applying NaBH4 or NaCNBH3 as stoichiometric reducing agent. The NO2 group reduction is highly chemoselective giving the corresponding anilines (17–91 % yields). The use of substoichiometric amounts of PQM allows more sustainable processes: reaction products are easily isolated and PQM can be directly recovered and recycled.